POPULARIZATION OF FOREIGN LANGUAGES - Sevinch Ochilova,; Liliya Iskandarova, (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
This article provides an understanding of foreign language teaching and learning methods and their application. It provides valuable information for teachers who are looking for effective language teaching methods and popularization of foreign language learning. Different approaches to teaching foreign languages are being discussed in educational institutions. The article also provides information about the importance of the integration of educational and scientific technologies and the importance of digital technologies in increasing the effectiveness of the lesson as a necessity.